A produção técnico-científica de James Precott Joule: uma leitura a partir da epistemologia de Ludwig Fleck - Queirós, Wellington Pereira de [UNESP]; Nardi, Roberto [UNESP]; Delizoicov, Demétrio (My University, 2014)
This paper aims an epistemologically analysis of the attempt of James Prescott Joule to replace the steam engine by the electric one. In this historical analysis, we use the epistemological categories: style of thinking, collective thinking, intercollective circulation of ideas and practices,Joule and other technicians in Machester received in that time financial incentives from governments and industry to replace the steam engine by the electric one, since it was in Manchester a culture of the technique of the accuracy and precision in which Joule was immersed, which allowed us to initially identify the styles of techniques thinking and experimental efficiency. However, Joule could not replace the steam engine by the electric; and the awareness of the problems faced by him, in the attempt to make such a substitution, led him to seek, through an intercollective circulation of ideas and practices, such as the studies of Faraday and Jacobi, a change of direction in his researches. According to our analysis, what happened was a change of style from a technical to a scientific thinking. In this sense, Joule began to investigate issues of a scientific nature, as the Joule’s effect and the mechanical equivalent of heat, which contributed significantly to the establishment of the principle of conservation of energy. We present here the contributions of this epistemological analysis to the discussion of questions of the nature of science in the basic education and for the training of physics teachers.

O presente trabalho tem por objetivo analisar epistemologicamente a tentativa de James Prescott Joule em substituir o motor a vapor pelo elétrico. Nesta análise histórica, utilizamos as categorias epistemológicas: estilo de pensamento, coletivo de pensamento, circulação intercoletiva de idéias e práticas e as conexões ativas e passivas de Ludwik Fleck. Joule e os demais técnicos de Manchester receberam incentivos financeiros de governos e industriais para substituírem o motor a vapor pelo elétrico, uma vez que havia em Manchester, naquela época, uma cultura da técnica e da busca da exatidão e precisão, na qual Joule estava imerso, o que nos permitiu identificar, inicialmente, estilos de pensamento tecnicista e de eficiência experimental. Entretanto, Joule não conseguiu substituir o motor a vapor pelo elétrico; e a consciência dos problemas enfrentados por ele, na tentativa de fazer tal substituição, levou-o a buscar, por meio da circulação intercoletiva de ideias e práticas, como o estudo dos trabalhos de Faraday e de Jacobi, uma reorientação de suas pesquisas. A partir de nossa análise, o que ocorreu foi uma mudança de estilo de pensamento do tecnicista para o científico. Nesse sentido, Joule passou a investigar questões de cunho científico, como o efeito Joule e o equivalente mecânico do calor, que contribuiu significativamente para o estabelecimento do princípio da conservação da energia. Apontamos, aqui, as contribuições desta análise epistemológica para a discussão de questões da natureza da ciência no ensino básico e na formação de professores de Física.
A technical-scientific production of James Prescott Joule: a reading from the epistemology of Ludwik Fleck
Keywords: Physics Teaching; Philosophy; History and Sociology of Science; Ludwik Fleck; James Prescott Joule; Ensino de Física; Filosofia; História e sociologia da ciência; Ludwik Fleck; James Prescott Joule